Positive electrode slurry and positive electrode for lithium secondary battery using the same
Preparing the positive electrode slurry through the dual-liquid composition solves the problems of dispersion and loss of irreversible additives in lithium secondary batteries, and achieves efficient improvement of electrical performance and extended battery life.
Patent Information
- Application Number
- CN202280005134.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-25
- Filing Date
- 2022-05-06
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-05-06
AI Technical Summary
In lithium secondary batteries, when irreversible additives are used, it is difficult to ensure high dispersion and low loss in the positive electrode slurry, resulting in deterioration of electrical performance and reduced freedom of process design.
The positive electrode slurry is prepared using a two-liquid composition. The first liquid contains a positive electrode active material, a positive electrode additive of a specific chemical formula and a conductive material. The second liquid contains a second positive electrode active material and a binder. The dispersion and processability are improved by adjusting the viscosity range (5000 cps to 10000 cps).
The high dispersion and low loss of the positive electrode additive are achieved, the electrical performance and state stability of the lithium secondary battery are improved, the electrode resistance is reduced, and the battery life is extended.
Smart Images

Figure BDA0004007670180000011 
Figure BDA0004007670180000141 
Figure BDA0004007670180000151
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode slurry and a positive electrode for a lithium secondary battery manufactured using the positive electrode slurry.
[0002] This application claims priority based on Korean Patent Application No. 10-2021-0067112 filed on May 25, 2021, and the entire contents of this Korean Patent Application are incorporated herein by reference. Background Art
[0003] As the technology development and demand for mobile devices increase, the demand for secondary batteries as energy sources is increasing sharply. Among these secondary batteries, lithium secondary batteries with high energy density and working potential, long cycle life and low self-discharge rate have been commercialized and widely used.
[0004] In recent years, as lithium secondary batteries are used as power sources for medium and large devices such as electric vehicles, lithium secondary batteries are further required to have high capacity, high energy density and low cost, and irreversible additives used in electrodes are also required to have higher irreversible capacity.
[0005] In response to the above needs, conventional irreversible additives such as Li6CoO4 have been developed. However, these irreversible additives are structurally unstable and can generate a large amount of oxygen (O2) when the secondary battery is charged as shown below, so the use of a large amount of irreversible additives in the positive electrode has limitations in terms of charging and discharging efficiency and safety of lithium secondary batteries:
[0006]
[0007] Therefore, efforts have been made to reduce the irreversibility of lithium secondary batteries by using a small amount of irreversible additives. However, when the irreversible additives are used in a small amount, especially in a small amount less than 5% by weight of the total weight of the positive electrode slurry, there are problems in that the electrical performance of the lithium secondary battery is deteriorated due to the difficulty in ensuring the dispersibility in the positive electrode slurry, and the loss amount of the irreversible additive increases due to the scattering of the irreversible additive with a small particle size during the manufacturing process of the positive electrode, so the degree of freedom of process design is reduced.
[0008] Therefore, it is necessary to develop a technology that can ensure excellent electrical performance of a lithium secondary battery by dispersing the irreversible additive in a positive electrode slurry when the irreversible additive is used.
[0009] [Prior art literature]
[0010] [Patent Document]
[0011] Korean Patent Publication No. 10-2019-0064423 Summary of the invention
[0012] [Technical issues]
[0013] The present technology aims to provide a positive electrode slurry containing a significantly small amount of an irreversible additive, wherein the irreversible additive has a high dispersion degree and is not lost when manufacturing the positive electrode, and a positive electrode for a lithium secondary battery manufactured using the positive electrode slurry.
[0014] [Technical solution]
[0015] The present technology aims to solve the above problems and provides a positive electrode slurry for a lithium secondary battery, which includes a mixture of a first liquid and a second liquid, wherein the first liquid contains a first positive electrode active material, a positive electrode additive represented by the following chemical formula 1 and a conductive material, and has a viscosity of 5000 cps or more and less than 8000 cps at 25±1°C; the second liquid contains a second positive electrode active material and a binder, wherein when the first liquid and the second liquid are mixed, the viscosity of the positive electrode slurry at 25±1°C is 8000 cps or more and less than 10000 cps:
[0016] [Chemical formula 1]
[0017] Li p Co (1-q) M 1 q O4
[0018] In Chemical Formula 1, M 1 It represents one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and p and q are 5≤p≤7 and 0≤q≤0.5, respectively.
[0019] The viscosity of the positive electrode slurry at 25±1° C. may be 8500 to 9700 cps.
[0020] The positive electrode additive may have a tetragonal structure with a space group of P42 / nmc.
[0021] The first liquid may contain 0.5 to 40 parts by weight of a positive electrode additive and 5 to 50 parts by weight of a conductive material relative to 100 parts by weight of the total amount of the first liquid, and the second liquid may contain 1 to 15 parts by weight of a binder relative to 100 parts by weight of the total amount of the second liquid.
[0022] The first positive electrode active material may be included in an amount of 1 to 30 parts by weight relative to 100 parts by weight of the entire positive electrode active material contained in the positive electrode slurry.
[0023] The first positive electrode active material and the second positive electrode active material may each be a lithium metal composite oxide represented by Chemical Formula 2 below:
[0024] [Chemical Formula 2]
[0025] Li x [Ni y Co z Mn w M 2 v O u
[0026] In Chemical Formula 2, M 2 represents one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and x, y, z, w, v, and u are 1.0 ≤ x ≤ 1.30, 0 ≤ y < 0.95, 0 < z ≤ 0.5, 0 < w ≤ 0.5, 0 ≤ v ≤ 0.2, and 1.5 ≤ u ≤ 4.5, respectively.
[0027] The weight average molecular weight (Mw) of the binder may be from 10,000 to 1,000,000.
[0028] The conductive material may include one or more materials selected from the group consisting of natural graphite, artificial graphite, carbon black, carbon nanotubes, graphene, acetylene black, Ketjen black, and carbon fiber.
[0029] Each of the first liquid and the second liquid may contain one or more polar aprotic solvents selected from N-methyl-2-pyrrolidone (NMP), N,N-dimethylacetamide (DMAc), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), acetonitrile (ACN), acetone, ethyl acetate, and distilled water.
[0030] The present technology aims to solve the above problems and provides a method for preparing a positive electrode paste for a lithium secondary battery, the method including: preparing a first liquid by mixing a first positive electrode active material, a positive electrode additive represented by Chemical Formula 1 below, and a conductive material, preparing a second liquid by mixing a second positive electrode active material and a binder, and preparing a positive electrode paste by mixing the first liquid and the second liquid, wherein the viscosity of the first liquid at 25 ± 1 °C is 5000 cps or more and less than 8000 cps, and the viscosity of the positive electrode paste at 25 ± 1 °C is 8000 cps or more and less than 10000 cps:
[0031] [Chemical Formula 1]
[0032] Li p Co (1-q) M 1q O4
[0033] In Chemical Formula 1, M 1 represents one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and p and q are 5≤p≤7 and 0≤q≤0.5, respectively. Here, the preparation of the first liquid can be carried out under a temperature condition of 40° C. or less.
[0034] [Beneficial Effects]
[0035] The positive electrode slurry for a lithium secondary battery of the present invention is composed of a two-liquid composition, contains a large amount of a positive electrode additive represented by Chemical Formula 1 used as an irreversible additive in the two-liquid composition, and contains a first liquid whose viscosity is adjusted to a specific range. Therefore, it not only has the advantages of excellent dispersibility and processability of the positive electrode additive, but also can suppress side reactions and minimize the loss of the positive electrode additive contained in the positive electrode slurry, thereby improving the state stability of the positive electrode slurry. Therefore, the electrical properties of the electrode manufactured using the positive electrode slurry are excellent. DETAILED DESCRIPTION
[0036] While the invention is susceptible to various modifications and alternative forms, specific embodiments thereof will be described in detail.
[0037] It should be understood, however, that there is no intent to limit the invention to the particular forms disclosed, but on the contrary, the invention is to cover all modifications, equivalents, and alternatives falling within the spirit and scope of the invention.
[0038] It should be further understood that when used herein, the terms “comprises,” “includes,” and / or “contains” specify the presence of stated features, integers, steps, operations, components, parts, or combinations thereof, but do not preclude the presence or addition of one or more other features, integers, steps, operations, components, parts, or combinations thereof.
[0039] In addition, when a layer, film, region or plate is referred to as being "formed on" another layer, film, region or plate, it includes a case where the layer, film, region or plate is directly formed on the other layer, film, region or plate and a case where another layer, film, region or plate is inserted between the layer, film, region or plate and the other layer, film, region or plate. Conversely, when a layer, film, region or plate is referred to as being "formed under" another layer, film, region or plate, it includes a case where the layer, film, region or plate is directly formed under the other layer, film, region or plate and a case where another layer, film, region or plate is inserted between the layer, film, region or plate and the other layer, film, region or plate. Furthermore, in this specification, when a component is referred to as being disposed "on" another component, it includes a case where the component is disposed above the other component and a case where the component is disposed below the other component.
[0040] In addition, in the present invention, "solid content" is the weight percentage of the solid material remaining after removing the solvent from the first liquid, the second liquid or the positive electrode slurry of the present invention based on its original weight. For example, when the weight of the solid material remaining after removing the solvent from 1 kg of the positive electrode slurry is 500g, the solid content of the positive electrode slurry is 50%.
[0041] In addition, in the present invention, "Ah" is a capacity unit of a lithium secondary battery, called "ampere-hour", which is the amount of current per hour. For example, when the capacity of a battery is "3000mAh", it means that the battery can be discharged at a current of 3000mA for 1 hour.
[0042] Hereinafter, the present invention will be described in more detail.
[0043] Cathode slurry for lithium secondary battery
[0044] In one embodiment, the present invention provides a positive electrode slurry for a lithium secondary battery, comprising a mixture of a first liquid and a second liquid, the first liquid containing a first positive electrode active material, a positive electrode additive represented by the following chemical formula 1, and a conductive material, and the first liquid has a viscosity of 5000 cps or more and less than 8000 cps at 25±1°C; the second liquid contains a second positive electrode active material and a binder, wherein when the first liquid and the second liquid are mixed, the viscosity of the positive electrode slurry at 25±1°C is 8000 cps or more and less than 10000 cps:
[0045] [Chemical formula 1]
[0046] Li p Co (1-q) M 1 q O4
[0047] In Chemical Formula 1, M 1It represents one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and p and q are 5≤p≤7 and 0≤q≤0.5, respectively.
[0048] The positive electrode slurry of the present technology is a composition for manufacturing a positive electrode used in a lithium secondary battery, and contains a positive electrode active material, a positive electrode additive, a conductive material and a binder required for manufacturing a positive electrode, wherein the individual components may exist separately from each other as two mixtures and then be mixed. In this case, the mixture may be in the form of a mixed solution, a dispersion and / or a solution.
[0049] Specifically, in the positive electrode slurry, a first liquid containing a first positive electrode active material, a positive electrode additive represented by Chemical Formula 1 and a conductive material and a second liquid containing a second positive electrode active material and a binder may exist separately from each other, and the first liquid and the second liquid may be mixed for use. The positive electrode slurry includes a first liquid obtained by pre-dispersing less than 5% by weight of a positive electrode additive and a conductive material in a solvent in large quantities together with some positive electrode active materials, thereby improving the dispersibility and processability of the positive electrode additive, and also improving the electrical performance and reliability of the manufactured positive electrode for a lithium secondary battery by minimizing the loss and side reactions of the positive electrode additive.
[0050] In this case, the first liquid may contain 0.5 to 40 parts by weight of a positive electrode additive and 5 to 50 parts by weight of a conductive material, relative to a total amount of 100 parts by weight of the first liquid. More specifically, the first liquid may contain 0.5 to 35 parts by weight, 0.5 to 25 parts by weight, 0.5 to 20 parts by weight, 0.5 to 15 parts by weight, 0.5 to 10 parts by weight, 0.5 to 5 parts by weight, 1 to 5 parts by weight, 1 to 15 parts by weight, 5 to 15 parts by weight, 0.5 to 5 parts by weight, 9 to 15 parts by weight, 11 to 15 parts by weight, 15 to 30 parts by weight, or 25 to 35 parts by weight of a positive electrode additive, relative to a total amount of 100 parts by weight of the first liquid. In this case, the amount of the positive electrode additive contained in the positive electrode slurry may be 5 parts by weight or less, more specifically 0.01 to 5 parts by weight, 0.01 to 3 parts by weight, 0.01 to 2 parts by weight, 0.5 to 2 parts by weight, 1 to 2.5 parts by weight, or 0.05 to 0.9 parts by weight, relative to 100 parts by weight of the total amount of the positive electrode slurry, especially relative to 100 parts by weight of the total solid content contained in the positive electrode slurry.
[0051] In addition, the first liquid may contain 5 to 40 parts by weight, 5 to 30 parts by weight, 5 to 20 parts by weight, 5 to 10 parts by weight, 10 to 20 parts by weight, 15 to 30 parts by weight, or 20 to 30 parts by weight of the conductive material, relative to 100 parts by weight of the total amount of the first liquid.
[0052] In addition, the second liquid may contain 1 to 10 parts by weight, 1 to 5 parts by weight, 2 to 6 parts by weight, 5 to 15 parts by weight, 5 to 10 parts by weight, 3 to 8 parts by weight, or 1 to 3 parts by weight of the binder, relative to 100 parts by weight of the total amount of the second liquid.
[0053] In addition, relative to the total amount of 100 parts by weight of the positive electrode active material contained in the positive electrode slurry, that is, the first positive electrode active material and the second positive electrode active material, the content of the first positive electrode active material contained in the first liquid may be 1 to 30 parts by weight. More specifically, relative to the total amount of 100 parts by weight of the first and second positive electrode active materials, the content of the first positive electrode active material may be 2 to 25 parts by weight, 2 to 20 parts by weight, 2 to 15 parts by weight, 2 to 10 parts by weight, 4 to 25 parts by weight, 5 to 20 parts by weight, 10 to 20 parts by weight, 3 to 8 parts by weight, 8 to 18 parts by weight, or 17 to 26 parts by weight.
[0054] According to the present technology, by controlling the amount of each component contained in the first liquid and the second liquid within the above-mentioned range, a small amount of positive electrode additive can be prevented from being lost in the form of dust when preparing the positive electrode slurry and a side reaction with moisture and / or oxygen in the air can be prevented, and the positive electrode additive can also be uniformly dispersed in the positive electrode slurry.
[0055] Meanwhile, the positive electrode additive may be lithium cobalt oxide represented by the following Chemical Formula 1.
[0056] [Chemical formula 1]
[0057] Li p Co (1-q) M 1 q O4
[0058] In Chemical Formula 1, M 1 It represents one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and p and q are 5≤p≤7 and 0≤q≤0.5, respectively.
[0059] The positive electrode additive may contain excess lithium to provide lithium for lithium consumption caused by irreversible chemical and physical reactions occurring at the negative electrode during initial charging, thereby increasing the charge capacity of the battery and reducing the irreversible capacity of the battery, thereby improving the life characteristics of the battery.
[0060] Among the positive electrode additives, the positive electrode additive represented by the above chemical formula 1 has a higher lithium ion content than the nickel-containing oxide commonly used in the art, so it can replenish the lithium ions lost due to irreversible reactions during the initial activation of the battery, thereby significantly improving the charge / discharge capacity of the battery. In addition, compared with the iron-containing and / or manganese-containing oxides commonly used in the art, there is no side reaction due to the dissolution of transition metals during the charge and discharge of the battery, so the battery has excellent stability. The lithium metal oxide represented by chemical formula 1 may include Li6CoO4, Li6Co 0.5 Zn 0.5 O4 or Li6Co 0.7 Zn 0.3 O4, etc.
[0061] In addition, the positive electrode additive represented by Chemical Formula 1 may have a tetragonal crystal structure and may be contained in the P42 / nmc space group, which has a distorted tetrahedral structure formed by cobalt elements and oxygen elements in the tetragonal crystal structure. Since the positive electrode additive has a distorted tetrahedral structure formed by cobalt elements and oxygen elements, the positive electrode additive may be structurally unstable, resulting in a side reaction with moisture or oxygen in the air at a temperature exceeding 40°C. However, the advantage of the present technology is that when the positive electrode additive is used to prepare a positive electrode slurry, a first liquid in which some positive active materials and positive electrode additives are pre-dispersed is used, so that the positive electrode additive can be prevented from having a side reaction with moisture or oxygen in the air.
[0062] In addition, since the first positive electrode active material and the second positive electrode active material respectively contained in the first liquid and the second liquid are positive electrode active materials capable of reversible insertion and deinsertion, each of them may include a lithium metal composite oxide represented by the following Chemical Formula 2 as a main component, and the lithium metal composite oxides used as the first positive electrode active material and the second positive electrode active material may be the same or different.
[0063] [Chemical formula 2]
[0064] Li x [Ni y Co z Mn w M 2 v ]O u
[0065] In Chemical Formula 2, M 2represents one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and x, y, z, w, v, and u are 1.0 ≤ x ≤ 1.30, 0 ≤ y < 0.95, 0 < z ≤ 0.5, 0 < w ≤ 0.5, 0 ≤ v ≤ 0.2, and 1.5 ≤ u ≤ 4.5, respectively.
[0066] The lithium metal composite oxide represented by Chemical Formula 2 is a composite metal oxide containing lithium and nickel, and may include one or more compounds selected from the group consisting of LiCoO2, LiCo 0.5 Zn 0.5 O2, LiCo 0.7 Zn 0.3 O2, LiNiO2, LiNi 0.5 Co 0.5 O2, LiNi 0.6 Co 0.4 O2, LiNi 1 / 3 Co 1 / 3 Al 1 / 3 O2, LiMnO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O2, and LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O2.
[0067] As an example, in the positive electrode active material, as the lithium metal composite oxide represented by Chemical Formula 2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2 can be used alone or in combination.0.8 Co 0.1 Mn 0.05 Al 0.05 O2 or LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O2.
[0068] In addition, the amount of the positive electrode active material may be 85 to 95 parts by weight, specifically 88 to 95 parts by weight, 90 to 95 parts by weight, 86 to 90 parts by weight, or 92 to 95 parts by weight, relative to 100 parts by weight of the positive electrode mixture layer.
[0069] In addition, the conductive material contained in the first liquid is used to improve the electrical properties of the positive electrode, and those commonly used in the art can be applied. Specifically, as the conductive material, one or more carbon-based materials selected from the group consisting of natural graphite, artificial graphite, carbon nanotubes, graphene, carbon black, acetylene black, Ketjen black and carbon fiber can be used. For example, the conductive material can be included in the form of a mixture of acetylene black and carbon nanotubes.
[0070] In addition, the content of the conductive material may be 1 to 5 parts by weight, specifically, 1 to 4 parts by weight, 2 to 4 parts by weight, 1.5 to 5 parts by weight, or 1 to 3 parts by weight, relative to 100 parts by weight of the mixture layer.
[0071] In addition, the binder is used to bind the positive active material, the positive electrode additive and the conductive material to each other, and any binder having this function can be used without particular limitation. Specifically, the binder may include one or more resins selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVdF-co-HFP), polyvinylidene fluoride (PVdF), polyacrylonitrile, polymethyl methacrylate and copolymers thereof. As an example, the binder may include polyvinylidene fluoride.
[0072] In addition, the weight average molecular weight (Mw) of the binder may be 10000 to 1000000, specifically, 100000 to 500000, 500000 to 1000000, 300000 to 700000, or 400000 to 600000. In the present technology, by controlling the weight average molecular weight (Mw) of the binder within the above range, the viscosity of the first liquid and the positive electrode slurry can be easily controlled.
[0073] In addition, the first liquid and the second liquid can each further contain a solvent. As a solvent, the first liquid and the second liquid can each contain one or more polar aprotic solvents such as N-methyl-2-pyrrolidone (NMP), N, N-dimethylacetamide (DMAc), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), acetonitrile (ACN), acetone, ethyl acetate and distilled water, and the solvent of the first liquid and the solvent of the second liquid can be the same or different from each other. As an example, the first liquid and the second liquid can each contain NMP as a solvent. In the present technology, by containing the above-mentioned solvent in the first liquid and the second liquid, the viscosity of the first liquid and the second liquid can be easily controlled, and the volatilization rate of the solvent can be appropriately controlled so that cracks will not be generated in the mixture layer due to the rapid volatilization of the solvent when the positive electrode is manufactured.
[0074] In addition, the viscosity of the first liquid and the positive electrode slurry of the present technology can be adjusted within a certain range. Specifically, the viscosity of the first liquid at 25 ± 1 ° C can be 5000cps or more and less than 8000cps. For example, the viscosity of the first liquid at 25 ± 1 ° C can be 5500cps or more and less than 8000cps, 6000cps or more and less than 8000cps, 6500cps or more and less than 8000cps, 7000cps or more and less than 8000cps, 5000cps or more and less than 7500cps, 5000cps or more and less than 7000cps, 5000cps or more and less than 6500cps, 6000cps or more and less than 7500cps, or 6500cps or more and less than 7500cps. In addition, the viscosity of the positive electrode slurry at 25±1° C. may be 8000cps to less than 9000cps, 8000cps to less than 8500cps, 8500cps to less than 10000cps, 9000cps to less than 10000cps, 8500cps to less than 9700cps, 8500cps to less than 9500cps, or 9000cps to less than 9800cps.
[0075] In the present technology, by controlling the viscosity of the first liquid and the positive electrode slurry within the above range, a small amount of positive electrode additives can be more evenly dispersed in the positive electrode slurry, the slurry can be evenly coated on the positive electrode collector and dried when manufacturing the positive electrode, and the electrical performance can be improved by reducing the electrode resistance of the manufactured battery. In addition, it can be prevented that the positive electrode mixture layer is unevenly formed during the manufacture of the positive electrode or the adhesion between the positive electrode mixture layer and the current collector is reduced due to the low viscosity of the first liquid and / or the positive electrode slurry.
[0076] Method for preparing positive electrode slurry for lithium secondary battery
[0077] In addition, in one embodiment, the present invention provides a method for preparing the above-mentioned positive electrode slurry for lithium secondary batteries.
[0078] The method for preparing positive electrode slurry of the present technology is carried out by preparing and mixing a first liquid containing a first positive electrode active material, a positive electrode additive and a conductive material and a second liquid containing a second positive electrode active material and a binder. Specifically, the method for preparing positive electrode slurry includes: mixing a first positive electrode active material, a positive electrode additive represented by the following chemical formula 1 and a conductive material to prepare the first liquid, mixing a second positive electrode active material and a binder to prepare the second liquid, and mixing the first liquid and the second liquid to prepare positive electrode slurry.
[0079] [Chemical formula 1]
[0080] Li p Co (1-q) M 1 q O4
[0081] In Chemical Formula 1, M 1 It represents one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and p and q are 5≤p≤7 and 0≤q≤0.5, respectively.
[0082] Here, the preparation of the first liquid and the preparation of the second liquid respectively include: mixing the first positive active material, the positive electrode additive and the conductive material to prepare the first liquid, and mixing the second positive active material and the binder to prepare the second liquid, and can be carried out under conventional conditions for preparing slurry in the art. For example, the preparation of the first liquid and the preparation of the second liquid can each be carried out as follows: adding each component to a homogenizer and stirring the liquid at 1000 to 5000 rpm in the homogenizer for 30 to 600 minutes, and the viscosity of the liquid at 25±1°C can be controlled while adding a solvent thereto during stirring. As an example, in the case of preparing the first liquid, the first positive active material, the positive electrode additive represented by Chemical Formula 1 and the conductive material can be added to the homogenizer, and the N-methylpyrrolidone solvent can be added to the homogenizer, while the above-mentioned added components are mixed at 3000 rpm for 60 minutes to prepare a first liquid having a viscosity of 7500±300cps at 25±1°C.
[0083] In addition, the preparation of the first liquid can be carried out under a temperature condition that satisfies a specific range to prevent the structurally unstable positive electrode additive from being damaged. Specifically, the preparation of the first liquid can be carried out under a temperature condition of 40°C or less, more specifically, it can be carried out under a temperature condition of 10°C to 40°C, 10°C to 35°C, 10°C to 30°C, 10°C to 25°C, 10°C to 20°C, 15°C to 40°C, 20°C to 40°C, 15°C to 35°C, or 18°C to 30°C.
[0084] In addition, the first liquid prepared in this manner can satisfy a certain viscosity range, specifically, the viscosity at 25±1°C is 5000cps or more and less than 8000cps, and in this case, the viscosity can be adjusted according to the type and / or amount of the positive electrode additive contained in the first liquid, the solid content, the type of solvent, etc., but the present technology is not limited thereto. For example, the viscosity of the first liquid at 25±1°C can be 5500cps or more and less than 8000cps, 6000cps or more and less than 8000cps, 6500cps or more and less than 8000cps, 7000cps or more and less than 8000cps, 5000cps or more and less than 7500cps, 5000cps or more and less than 7000cps, 5000cps or more and less than 6500cps, 6000cps or more and less than 7500cps, or 6500cps or more and less than 7500cps.
[0085] In addition, the preparation of the positive electrode slurry is an operation of preparing the positive electrode slurry by mixing the first liquid and the second liquid prepared in advance, and in this case, the mixing can be carried out by a method commonly used in the art without particular limitation, specifically, the mixing can be carried out by adding any one of the first liquid and the second liquid to the other composition. In some cases, the mixing can be carried out while the first liquid and the second liquid are simultaneously added to a mixer or a reactor, etc.
[0086] In addition, the positive electrode slurry prepared in this manner may have a higher viscosity than the first liquid. Specifically, the viscosity of the positive electrode slurry at 25 ± 1 ° C may be 8000 cps or more and less than 10000 cps. For example, the viscosity of the positive electrode slurry at 25 ± 1 ° C may be 8000 cps or more and less than 9000 cps, 8000 cps or more and less than 8500 cps, 8500 cps or more and less than 10000 cps, 9000 cps or more and less than 10000 cps, 8500 cps or more and less than 9700 cps, 8500 cps or more and less than 9500 cps, or 9000 cps or more and less than 9800 cps.
[0087] In the present technology, when preparing the positive electrode slurry, by controlling the viscosity of the first liquid and the positive electrode slurry within the above range, a small amount of positive electrode additives can be more evenly dispersed in the positive electrode slurry, the slurry can be evenly coated on the positive electrode collector and dried during the manufacture of the positive electrode, and the electrical performance can be improved by reducing the electrode resistance of the manufactured battery. In addition, it can be prevented that the positive electrode mixture layer is unevenly formed during the manufacture of the positive electrode, or the adhesion between the positive electrode mixture layer and the current collector is reduced during the manufacture of the positive electrode due to the low viscosity of the first liquid and / or the positive electrode slurry.
[0088] Positive electrode for lithium secondary battery
[0089] In addition, in one embodiment, the present invention provides a positive electrode for a lithium secondary battery, which includes a positive electrode current collector and a positive electrode mixture layer manufactured using the positive electrode slurry of the present technology.
[0090] The positive electrode for lithium secondary battery of the present technology includes a positive electrode mixture layer manufactured by coating the positive electrode slurry of the present technology on a positive electrode collector, drying and pressing, and the positive electrode mixture layer has a configuration containing a positive electrode active material, a positive electrode additive represented by Chemical Formula 1, a conductive material and a binder.
[0091] In this case, the average thickness of the positive electrode mixture layer is not particularly limited, but specifically, it can be 50μm to 300μm, more specifically, it can be 100μm to 200μm, 80μm to 150μm, 120μm to 170μm, 150μm to 300μm, 200μm to 300μm, or 150μm to 190μm.
[0092] In addition, as the positive electrode current collector of the positive electrode, a material having high conductivity and not causing chemical changes in the battery can be used. For example, stainless steel, aluminum, nickel, titanium or calcined carbon, etc. can be used, and when aluminum or stainless steel is used, a material whose surface is treated with carbon, nickel, titanium or silver, etc. can be used. In addition, the positive electrode current collector may be formed with fine concave and convex objects on its surface to increase the adhesion of the positive electrode active material, and may be formed in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics. In addition, considering the conductivity and total thickness of the positive electrode to be manufactured, the average thickness of the positive electrode current collector may be appropriately applied in the range of 3 to 500 μm.
[0093] Lithium secondary battery
[0094] Furthermore, in one embodiment, the present invention provides a lithium secondary battery including the positive electrode of the present technology described above, a negative electrode, and a separator disposed between the positive electrode and the negative electrode.
[0095] The lithium secondary battery of the present technology includes the positive electrode of the present technology described above, so that during the initial charging, delithiation of the positive electrode additive can be induced at a high rate under low voltage conditions less than or equal to the allowable voltage. Therefore, the amount of oxygen generated during subsequent charging and discharging is significantly less, and thus the advantages are that the electrical performance and safety of the lithium secondary battery are excellent.
[0096] The lithium secondary battery of the present technology has a structure including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode.
[0097] Here, the negative electrode can be manufactured by coating, drying, and pressing a negative electrode active material on a negative electrode current collector, and if necessary, may optionally further include the same conductive material, organic binder polymer, additives, etc. as in the positive electrode.
[0098] In addition, examples of the negative electrode active material may include: graphite having a complete layered crystal structure such as natural graphite, soft carbon having a low-crystalline layered crystal structure (graphene structure; a structure in which a hexagonal honeycomb plane arrangement of carbon forms layers), and graphite materials in which carbon and these structures are mixed with an amorphous part, such as hard carbon, artificial graphite, expanded graphite, carbon fiber, non-graphitized carbon, carbon black, carbon nanotubes, fullerenes, and activated carbon, etc., metal composite oxides, such as Li x Fe2O3(0 ≤ x ≤ 1), Li x WO2(0 ≤ x ≤ 1), Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’, Al, B, P, Si, elements of Group 1, Group 2, Group 3 of the periodic table, halogens; 0 < x ≤ 1; 1 ≤ y ≤ 3; and 1 ≤ z ≤ 8), etc., lithium metal, lithium alloy, silicon-based alloy, tin-based alloy, metal oxides, such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5, etc., conductive polymers, such as polyacetylene, etc., Li-Co-Ni-based materials, titanium oxides, and lithium titanium oxides, etc.
[0099] As an example, the negative electrode active material may include graphite and silicon (Si)-containing particles. The graphite may include any one or more of natural graphite having a layered crystal structure and artificial graphite having an isotropic structure, and the silicon (Si)-containing particles may include silicon (Si) particles, silicon oxide (SiO2) particles, or a mixture of silicon (Si) particles and silicon oxide (SiO2) particles as particles mainly composed of silicon (Si) serving as a metal component.
[0100] In this case, the negative electrode active material may include 80 to 95 parts by weight of graphite and 1 to 20 parts by weight of silicon (Si) particles relative to 100 parts by weight of the total amount of the negative electrode active material. In the present technology, by adjusting the amount of graphite and silicon (Si) particles contained in the negative electrode active material within the above range, the charging capacity per unit mass can be increased while reducing lithium consumption and irreversible capacity loss during initial charging and discharging of the battery.
[0101] In addition, the negative electrode mixture layer may further include a binder to adhere the negative electrode active material to the negative electrode current collector. For example, the negative electrode mixture layer may include any one or a mixture of two or more of PVdF, polyacrylic acid (PAA), polymethacrylic acid (PMMA), styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC) as a binder.
[0102] In this case, the amount of the binder may be 0.5 to 5 parts by weight, specifically 0.5 to 4 parts by weight or 1 to 3 parts by weight, relative to 100 parts by weight of the negative electrode mixture layer.
[0103] In addition, the negative electrode mixture layer may have an average thickness of 100 to 200 μm, specifically, the average thickness may be 100 to 180 μm, 100 to 150 μm, 120 to 200 μm, 140 to 200 μm, or 140 to 160 μm.
[0104] In addition, the negative electrode current collector is not particularly limited to any current collector as long as it has high conductivity and does not cause chemical changes in the battery, and for example, the negative electrode current collector can use copper, stainless steel, nickel, titanium or calcined carbon, etc., and when copper or stainless steel is used, a material whose surface is treated with carbon, nickel, titanium or silver, etc. can be used. In addition, like the positive electrode current collector, the negative electrode current collector can be formed with fine concavoconvex objects on its surface to strengthen the binding force with the negative electrode active material, and can be formed into various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics. In addition, considering the conductivity and total thickness of the negative electrode to be manufactured, the average thickness of the negative electrode current collector can be appropriately applied in the range of 3 to 500 μm.
[0105] In addition, the separator is placed between the positive electrode and the negative electrode, and an insulating film with high ion permeability and mechanical strength is used as the separator. The separator is not particularly limited as long as it is commonly used in the art, but specifically, a sheet or non-woven fabric made of chemically resistant and hydrophobic polypropylene, glass fiber or polyethylene, etc. can be used, and in some cases, a composite separator can be used, in which a porous polymer substrate (such as a sheet or non-woven fabric) is coated with inorganic particles / organic particles by an organic binder polymer. When a solid electrolyte such as a polymer is used as an electrolyte, the solid electrolyte can also serve as a separator. In addition, the average pore size of the separator can be 0.01 to 10 μm and the average thickness can be 5 to 300 μm.
[0106] Meanwhile, the positive electrode and the negative electrode may be wound in a roll core form and may be accommodated in a cylindrical battery, a prismatic battery, or a pouch type battery, or accommodated in a pouch type battery in a folded or stack-folded form, but the present technology is not limited thereto.
[0107] In addition, the lithium salt-containing electrolyte of the present technology may be composed of an electrolyte and a lithium salt, and the lithium salt-containing electrolyte may use a non-aqueous organic solvent, an organic solid electrolyte, an inorganic solid electrolyte, and the like.
[0108] Examples of non-aqueous organic solvents may include aprotic organic solvents such as N-methyl-2-pyrrolidone, ethylene carbonate (EC), propylene carbonate, butylene carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), γ-butyrolactone, 1,2-dimethoxyethane, tetrahydroxyfranc, 2-methyltetrahydrofuran, DMSO, 1,3-dioxolane, formamide, DMF, dioxolane, ACN, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, ethyl propionate, and the like.
[0109] Examples of the organic solid electrolyte may include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, poly-agitated lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, polymer materials containing ion dissociative groups, and the like.
[0110] Examples of inorganic solid electrolytes may include Li nitrides, halides, sulfates, and the like, such as Li3N, LiI, Li5Ni2, Li3N-LiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, Li3PO4-Li2S-SiS2, and the like.
[0111] Lithium salts are materials that are easily soluble in non-aqueous electrolytes, and examples of lithium salts may include LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)2NLi, lithium chloroborane, lithium lower aliphatic carboxylate, lithium tetraphenylborate, imide, etc.
[0112] In addition, in order to improve charging and discharging characteristics, flame retardancy, etc., pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, aluminum chloride, etc. may be added to the electrolyte. In some cases, in order to impart non-flammability, a halogen-containing solvent such as carbon tetrachloride, trifluoroethylene, etc. may be further included, and in order to improve high-temperature storage characteristics, carbon dioxide gas may be further included, and fluoroethylene carbonate (FEC), propylene sultone (PRS), etc. may be further included.
[0113] Example
[0114] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples.
[0115] However, the embodiments and comparative examples described below are intended only to illustrate the present technology, and the contents of the present technology are not limited to the embodiments and comparative examples described below.
[0116] Examples 1 to 4 and Comparative Examples 1 to 8. Preparation of positive electrode slurry
[0117] LiNi as the first positive electrode active material was prepared 0.6 Co 0.2 Mn 0.2 O2, Li6Co as a cathode additive 0.7 Zn 0.3 O4, acetylene black as a conductive material and carbon nanotubes (weight ratio of 93 to 97:3 to 7) were weighed as shown in Tables 1 and 2 below and added to a homogenizer, and then N-methylpyrrolidone solvent was introduced into the homogenizer and mixed at 3000 rpm for 60 minutes to prepare a first liquid.
[0118] Separately, LiNi as the second positive electrode active material was prepared. 0.6 Co 0.2 Mn 0.2O2 and PVdF (weight average molecular weight Mw: 500000±25000) as a binder were weighed as shown in Tables 1 and 2 below and added to a homomixer, and then N-methylpyrrolidone solvent was introduced into the homomixer and mixed at 3000 rpm for 90 minutes to prepare a second liquid.
[0119] When the second liquid was prepared, the first liquid prepared in advance was added to the homomixer and further mixed for 30 minutes to prepare a positive electrode slurry. In this case, the viscosity of the first liquid and the positive electrode slurry at 25° C. was adjusted as shown in Tables 1 and 2.
[0120] [Table 1]
[0121]
[0122] [Table 2]
[0123]
[0124] Comparative Example 9. Preparation of positive electrode slurry
[0125] N-methylpyrrolidone solvent was introduced into a homogenizer, and 93 parts by weight of LiNi as the positive electrode active material was weighed. 0.6 Co 0.2 Mn 0.2 O2, 3 parts by weight of Li6Co as a positive electrode additive 0.7 Zn 0.3 O4, 2 parts by weight of acetylene black and carbon nanotubes as conductive materials (weight ratio of 93 to 97: 3 to 7) and 2 parts by weight of PVdF (weight average molecular weight Mw: 500000 ± 25000) as a binder, and added to a homogenizer, and then mixed at 3000 rpm for 60 minutes to prepare a positive electrode slurry. In this case, the viscosity of the prepared positive electrode slurry at 25 ° C was 9500 cps.
[0126] Experimental example
[0127] The positive electrode slurry prepared in each of Examples and Comparative Examples was coated on one surface of an aluminum current collector, dried and roll-pressed at 100° C. to manufacture a positive electrode. In this case, the total thickness of the positive electrode mixture layer was 130 μm, and the total thickness of the manufactured positive electrode was about 200 μm.
[0128] In addition, natural graphite and silicon (SiO) were prepared as negative electrode active materials. x, wherein 1≤x≤2) particles and SBR as a binder, and the negative electrode slurry is prepared in the same manner as the positive electrode slurry. In this case, the graphite used in the manufacture of the negative electrode mixture layer is natural graphite (average particle size: 0.01 to 0.5 μm), and silicon (SiO) with an average particle size of 0.9 to 1.1 μm is used. x ) particles. The prepared negative electrode slurry was coated on one surface of a copper current collector, dried at 100° C. and roll-pressed to manufacture a negative electrode. In this case, the total thickness of the negative electrode mixture layer was 150 μm, and the total thickness of the manufactured negative electrode was about 250 μm.
[0129] Then, a separator (thickness: about 16 μm) made of a porous polyethylene (PE) film was placed between the manufactured positive electrode and negative electrode, and E2DVC as an electrolyte was added to manufacture a full-cell type battery cell.
[0130] Here, "E2DVC" is a carbonate-based electrolyte solution obtained by mixing lithium hexafluorophosphate (LiPF6, 1.0 M) and ethylene carbonate (VC, 2 wt%) in a mixture of EC:DMC:DEC=1:1:1 (volume ratio).
[0131] In order to evaluate the performance of the positive electrode additive of the present technology, the following experiment was conducted using the lithium secondary battery cell manufactured as described above.
[0132] A) Measure the amount of oxygen produced during charging and discharging
[0133] For the lithium secondary battery manufactured using the positive electrode slurry of the embodiment and the comparative example, the initial charge (formation) was performed at 55°C under the conditions of 3.6V and 1.0C, and while performing the initial charge, the gas generated by the positive electrode was degassed, and the amount of oxygen generated during the initial charge was analyzed. Then, 50 charges and discharges were repeated at 45°C under the condition of 0.3C, and the amount of oxygen generated due to the decomposition of the electrolyte during each charge / discharge was further analyzed, and the analysis results are shown in Table 3 below.
[0134] B) Measure the initial resistance
[0135] For the lithium secondary batteries manufactured using the positive electrode slurries of Examples and Comparative Examples, the state of charge (SoC) was adjusted to 50% and then rapidly discharged for 10 seconds to measure the resistance of the secondary batteries, and the measurement results are shown in Table 3 below.
[0136] C) Evaluation of the charge / discharge capacity and retention rate of lithium secondary batteries
[0137] The lithium secondary batteries manufactured using the positive electrode slurries of the embodiments and comparative examples were charged at a temperature of 25° C. with a charging current of 0.1 C to a final charge voltage of 4.2 V, and activated by charging at the final voltage until the current density reached 0.01 C. Then, the lithium secondary batteries were discharged at a discharge current of 0.1 C to a final voltage of 2.5 V, and the initial charge / discharge capacity per unit mass was measured.
[0138] Then, charging and discharging were repeated 50 times at 45° C. under the condition of 0.3 C while measuring the charge / discharge capacity, and after charging and discharging 50 times, the charge / discharge capacity retention ratio was calculated. The calculation results are shown in Table 3 below.
[0139] [Table 3]
[0140]
[0141] As shown in Table 3, in the positive electrode slurry of the present technology, it can be confirmed that the positive electrode additive suppresses the loss and / or side reaction of the positive electrode additive during preparation, and the positive electrode additive is uniformly dispersed, so the amount of oxygen generated during charging and discharging is low and exhibits high capacity and long life.
[0142] Specifically, when the positive electrode slurry prepared in the embodiment is used, it is found that the lithium secondary battery generates 80 to 110 ml / g of oxygen during initial charge and discharge, and generates less than 15 ml / g of oxygen during subsequent charge and discharge. This means that when the positive electrode slurry is prepared, the positive electrode additive is uniformly dispersed therein, and an irreversible reaction is efficiently performed in the slurry during initial charge and discharge.
[0143] In addition, it was confirmed that the positive electrode slurry prepared in the example was in a form in which the positive electrode additive was uniformly dispersed therein, and thus had a low electrode surface resistance of 10 3 Ω or less.
[0144] In addition, it was confirmed that when the positive electrode slurry of the embodiment was used to manufacture the electrode, the initial charge / discharge capacity and the capacity retention rate had high values of 103 mAh or more and 90% or more, respectively. This means that when the positive electrode slurry is prepared, the positive electrode additive in powder form is prevented from being lost during the mixing of the positive electrode additive or the activity of the positive electrode slurry is prevented from being reduced due to a side reaction with moisture and / or oxygen in the air.
[0145] According to the above results, the positive electrode slurry for lithium secondary batteries of the present technology is composed of a two-liquid composition, contains a large amount of the positive electrode additive represented by Chemical Formula 1 used as an irreversible additive, and contains a first liquid whose viscosity is adjusted to a specific range. Therefore, it not only has the advantages of excellent dispersibility and processability of the positive electrode additive, but also can suppress side reactions and minimize the loss of the positive electrode additive contained in the positive electrode slurry, thereby improving the state stability of the positive electrode slurry. Therefore, the electrical performance of the electrode manufactured using the positive electrode slurry is excellent.
[0146] Although exemplary embodiments of the present invention and their advantages have been described above in detail, those skilled in the art should understand that various changes, substitutions and alterations may be made herein without departing from the scope of the invention as defined by the following claims.
[0147] Therefore, the technical scope of the present invention should not be limited to the contents described in the detailed description of the specification but should be defined by the appended claims.
Claims
1. A positive electrode slurry for a lithium secondary battery, the positive electrode slurry comprising a mixture of a first liquid and a second liquid: The first liquid contains a first positive electrode active material, a positive electrode additive represented by the following Chemical Formula 1, and a conductive material, and has a viscosity at 25±1° C. of 5000 cps or more and less than 8000 cps; and The second liquid contains a second positive electrode active material and a binder, in, When the first liquid and the second liquid are mixed, the viscosity of the positive electrode slurry at 25±1° C. is greater than 8000 cps and less than 10000 cps: [Chemical formula 1] Li p Co (1-q) M 1 q O4 In Chemical Formula 1, M 1 represents one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and p and q are 5≤p≤7 and 0≤q≤0.5, respectively; Wherein, relative to 100 parts by weight of the total solid content contained in the positive electrode slurry, the amount of the positive electrode additive contained in the positive electrode slurry is greater than 0.05 parts by weight and less than 5 parts by weight; Wherein, relative to 100 parts by weight of the total amount of the positive electrode active material contained in the positive electrode slurry, the content of the first positive electrode active material is 1 part by weight to 30 parts by weight.
2. The positive electrode slurry according to claim 1, wherein The positive electrode slurry has a viscosity of 8500 to 9700 cps at 25±1° C.
3. The positive electrode slurry according to claim 1, wherein The positive electrode additive has a tetragonal crystal structure with a space group of P42 / nmc.
4. The positive electrode slurry according to claim 1, wherein The first liquid contains 0.5 to 40 parts by weight of the positive electrode additive and 5 to 50 parts by weight of the conductive material, relative to 100 parts by weight of the total amount of the first liquid.
5. The positive electrode slurry according to claim 1, wherein The second liquid contains 1 to 15 parts by weight of the binder relative to 100 parts by weight of the total amount of the second liquid.
6. The positive electrode slurry according to claim 1, wherein The content of the first positive electrode active material is 2 to 25 parts by weight relative to 100 parts by weight of the total amount of the positive electrode active material contained in the positive electrode slurry.
7. The positive electrode slurry according to claim 1, wherein: The first positive electrode active material and the second positive electrode active material are each a lithium metal composite oxide represented by the following Chemical Formula 2: [Chemical formula 2] Li x [Ni y Co z Mr w M 2 v ]O u In Chemical Formula 2, M 2 represents one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo, and x, y, z, w, v, and u are 1.0 ≤ x ≤ 1.30, 0 ≤ y < 0.95, 0 < z ≤ 0.5, 0 < w ≤ 0.5, 0 ≤ v ≤ 0.2, and 1.5 ≤ u ≤ 4.5, respectively.
8. The positive electrode slurry according to claim 1, wherein The binder has a weight average molecular weight (Mw) of 10,000 to 1,000,000.
9. The positive electrode slurry according to claim 1, wherein: The conductive material includes one or more materials selected from the group consisting of natural graphite, artificial graphite, carbon black, carbon nanotubes, graphene, and carbon fibers.
10. The positive electrode slurry according to claim 1, wherein: The conductive material includes one or more materials selected from the group consisting of acetylene black and Ketjen black.
11. The positive electrode slurry according to claim 1, wherein: The first liquid and the second liquid each contain one or more polar aprotic solvents selected from N-methyl-2-pyrrolidone (NMP), N,N-dimethylacetamide (DMAc), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), acetonitrile (ACN), acetone, ethyl acetate, and distilled water.
12. A method for preparing a positive electrode slurry for a lithium secondary battery, the method comprising: Mixing a first positive electrode active material, a positive electrode additive represented by the following Chemical Formula 1, and a conductive material to prepare a first liquid; mixing a second positive electrode active material and a binder to prepare a second liquid; and Mixing the first liquid and the second liquid to prepare a positive electrode slurry, wherein the viscosity of the first liquid at 25±1°C is greater than 5000 cps and less than 8000 cps, and The viscosity of the positive electrode slurry at 25±1° C. is greater than 8000 cps and less than 10000 cps: [Chemical formula 1] Li p Co (1-q) M 1 q O4 In Chemical Formula 1, M 1 represents one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B and Mo, and p and q are 5≤p≤7 and 0≤q≤0.5, respectively; Wherein, relative to 100 parts by weight of the total solid content contained in the positive electrode slurry, the amount of the positive electrode additive contained in the positive electrode slurry is greater than 0.05 parts by weight and less than 5 parts by weight; Wherein, relative to 100 parts by weight of the total amount of the positive electrode active material contained in the positive electrode slurry, the content of the first positive electrode active material is 1 part by weight to 30 parts by weight.
13. The method of claim 12, wherein: The preparation of the first liquid is carried out at a temperature below 40°C.
Citation Information
Patent Citations
Additives for cathode, manufacturing method of the same, cathode including the same, and lithium recharegable battery including the same
KR1020190064423A
Bag for containing bottle
KR1020210067112A
Method for manufacturing composition for forming cathode of lithium secondary battery, cathode manufactured by using composition, and lithium secondary battery
CN107112524A
Method for producing slurry composition for secondary battery positive electrode, positive electrode for secondary battery produced using same, and lithium secondary battery comprising same
CN110431697A